Phytochemical Background Mediates Effects of Pyrrolizidine Alkaloids on Western Flower Thrips - Liu, Xiaojie (J Chem Ecol, 2018)
Plants produce an extremely diverse array of metabolites that mediate many aspects of plant-environment interactions. In the context of plant-herbivore interactions, it is as yet poorly understood how natural backgrounds shape the bioactivity of individual metabolites. We tested the effects of a methanol extract of Jacobaea plants and five fractions derived from this extract, on survival of western flower thrips (WFT). When added to an artificial diet, the five fractions all resulted in a higher WFT survival rate than the methanol extract. In addition, their expected combined effect on survival, assuming no interaction between them, was lower than that of the methanol extract. The bioactivity was restored when the fractions were combined again in their original proportion. These results strongly suggest synergistic interactions among the fractions on WFT survival rates. We then tested the effects of two pyrrolizidine alkaloids (PAs), free base retrorsine and retrorsine N-oxide, alone and in combination with the five shoot fractions on WFT survival. The magnitude of the effects of the two PAs depended on the fraction to which they were added. In general, free base retrorsine was more potent than retrorsine N-oxide, but this was contingent on the fraction to which these compounds were added. Our results support the commonly held, though seldom tested, notion that the efficacy of plant metabolites with respect to plant defence is dependent on their phytochemical background. It also shows that the assessment of bioactivity cannot be decoupled from the natural chemical background in which these metabolites occur. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10886-018-1009-2) contains supplementary material, which is available to authorized users.